An Ohmic heating study of the functionality of leavening acids in cream cake systems. (December 2021) - Godefroidt, Thibault; Ooms, Nand; Bosmans, Geertrui; Brijs, Kristof; Delcour, Jan A.
Abstract: Temperature gradients during cake baking complicate the study of leavening agent functionality, as leavening acid solubility and dissolution rate determine the moment of carbon dioxide (CO2 ) production. To control batter temperature, cream cake batter was baked in an electrical resistance oven (ERO). Simultaneously, CO2 release in the ERO headspace and cake height were monitored. Furthermore, CO2 production and release were linked to thermal transitions in the cake batter (DSC) and crumb structure setting (RVA). Early-acting organic acids produced high amounts of CO2 during mixing which could not be retained. This yielded low volume cakes. Sodium acid pyrophosphate and late-acting organic acids resulted in high quality cakes. However, CO2 production after crumb setting did not (further) improve cake quality, which implies suboptimal use of leavening power. This study highlights the importance of CO2 production during the early baking phase and illustrates the value of the ERO set-up for studying leavening agents. Highlights: CO2 monitoring during Ohmic heating allows characterization of leavening action. CO2 production during the early baking phase is crucial for cream cake leavening. Cream cake batter cannot retain CO2 produced during mixing. CO2 production after structure setting equals suboptimal use of leavening power. Fumaric and adipic acid are promising sodium acid pyrophosphate alternatives.